Analisis Pengaruh Pengetahuan Zakat dan Pendapat terhadap Minat Menunaikan Zakat Pertanian pada Petani Kopi Desa Blau - Andri Frediansyah; Yosy Arisandy; Andi Harpepen (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
This study aims to determine the effect of zakat knowledge on interest in paying agricultural zakat, the effect of income on interest in paying agricultural zakat, the effect of zakat knowledge and income level simultaneously on interest in paying agricultural zakat, and the extent to which zakat knowledge and income influence interest in paying agricultural zakat among coffee farmers in Blau Village. This study used a quantitative research method using the Partial Least Squares (PLS) technique, including Outer Loading and Inner Loading tests. The sample size for this study was 30. The results showed that zakat knowledge did not influence coffee farmers' interest in paying agricultural zakat. Income level also did not influence coffee farmers' interest in paying agricultural zakat. Zakat knowledge (X1) and income level (X1) did not influence coffee farmers' interest in paying agricultural zakat (Y). The magnitude of the influence of these two variables on the dependent variable, interest in paying zakat, was 0.065. This shows that 6.5% of the variation in coffee farmers' interest in paying agricultural zakat, meanwhile, the remaining 93.5% is influenced by two other variables outside this research model.